Acid-Mediated Synthesis of Chromeno[2,3-b]pyridine Derivatives via Condensation of 2-Amino-3-formylchromones and 1-(Methylthio)-2-nitroenamine Derivatives - Yang, Hongchen; Zhang, Lu; Xu, Xiaoyong; Shao, Xusheng; Li, Zhong (Synlett, 2022)
A convenient and effective protocol has been proposed for the synthesis of chromeno[2,3-b]pyridine derivatives via the CF3SO3H-catalyzed annulation of substituted 2-amino-3-formylchromones and various 1-(methylthio)-2-nitroenamine derivatives. This method is time-efficient, convenient, high-yielding, and exhibits a good functional group compatibility.
Keywords: 2-amino-3-formylchromone derivatives; chromeno[2,3-b]pyridine derivatives; (E)-N-methyl-1-(methylthio)-2-nitroethenamine (NMSM)